Teknik Pemodelan Fisika dalam Setting Pembelajaran Berbasis Learner Autonomy - Abdul Salam (Jurnal Fisika FLUX, 2018)
Modeling technique is one of physics instructional technique required by physics student teacher in order to understand and apply various concept, principle, and law of physics. The importance of modeling technique in physics instructional has moved the research team to apply the physics modeling technique in the setting of learner autonomy based instructional. This study used one group pretest and posttest design. Subject of this study was the physics education study program student of FKIP ULM who recourse basic physics course in the academic year of 2016/2017. The instrument used in this study was the student achievement test. The data was analyzed in a descriptive-qualitative way and also quantitatively depends on the nature of the data. Result of the study showed that the implementation of physics modeling technique in the setting of learner autonomy based learning was effective to improve students’ basic competence knowledge with the gain score of 0.68, which is in medium category.